Cholesterol-lowering activity of lactic acid bacteria and yeast when used as probiotics in laying quail (Coturnix coturnix Japonica) - Istiqomah, L.; Sakti, A. A.; Sofyan, A.; Herdian, H.; Anggraeni, A. S. (Diponegoro University, 2020)
This study aimed to evaluate the administration of Lactobacillus plantarum AKK-30 and Saccharomyces cerevisiae B-18 as probiotics in reducing cholesterol of blood, egg, and meat and also the production performance of laying quail (Coturnix coturnix Japonica). A number of 600 birds of the twenty one-day-old quails were distributed in a completely randomized design with 5 treatments and 6 replications (initial BW= 101.35 ± 1.64 g). Treatments were as follows: A = negative control (basal diet without probiotic), B = 1% of L. plantarum AKK-30 (107 cfu/g), C = 1% of S. cerevisiae B-18 (106 cfu/g), D = 1% of a probiotic consortium, E = positive control (commercial probiotic). Parameters observed were blood biochemistry profiles, product quality, and production performance. The results revealed that administration of 1% S. cerevisiae (C) resulted the lowest cholesterol in blood (101.75 mg/dL) and egg (9.44 mg/g) and while administration of 1% L. plantarum(B) increased meat protein and decreased fat content (P<0.05). Level of blood triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) were not different among treatments. Probiotic treatments did not affect the growth performance, quail day production (QDP), feed conversion ratio (FCR) and egg uniformity. However, probiotic increased diameter of egg yolk (P<0.05). It was concluded that administration of single probiotic L. plantarum AKK-30 or S. cerevisiae B-18 improves the quality of laying quail products.